Fe1−xS/nitrogen and sulfur Co-doped carbon composite derived from a nanosized metal–organic framework for high-performance lithium-ion batteries. Issue 1 (24th October 2018) - Liu, Yingying; Zhong, Ming; Kong, Lingjun; Li, Ang; Sun, Xiaowen; Wang, Danhong; Bu, Xian-He
Abstract : Fe1− x S/NSC composite was prepared as an anode for LIBs by a one-step pyrolysis approach, and it exhibited outstanding cycle stability and rate performance. Abstract : Iron sulfide (Fe1− x S), possessing unique superiorities, including high theoretical capacity, easy access to raw materials, and environment friendliness, has stood out from various anode materials of lithium-ion batteries (LIBs). However, there are still some critical obstacles that need to be overcome before its practical applications. For instance, the huge volume change that occurs during the lithium ion insertion/extraction process leads to a rapid decay in electrochemical performance. Moreover, it is generally difficult to achieve a perfect rate performance for Fe1− x S due to its poor intrinsic conductivity. Herein, we have reported a facile method to synthesize a Fe1− x S/N, S co-doped carbon composite (Fe1− x S/NSC) using a nanosized Fe-based metal–organic framework as the precursor. Compared with Fe1− x S, the as-synthesized Fe1− x S/NSC composite exhibited higher cycling stability and rate capability as an anode for LIBs. For example, a high specific capacity of 1135 mA h g −1 (0.1 A g −1 ) and 707 mA h g −1 (1 A g −1 ) could be maintained after 100 cycles and 200 cycles, respectively. Most impressively, a reversible capacity of 586 mA h g −1 was delivered at higher density of 5 A g −1 in the rate test.